Promotion And Campaigning for The Presidential Election in New Uzbekistan - Sadikova Yorkinoy Salijanovna; Abdijalilov Elyor Shuxrat oʻgʻli (Zien Journals, 2021)
The article presents views on the electoral process and the activities of electoral bodies in Uzbekistan, the state of electoral freedom in Uzbekistan and the development of electoral legislation.
Keywords: State; citizen; society; elections